Future Warming and Intensification of Precipitation Extremes: A "Double Whammy" Leading to Increasing Flood Risk in California. Issue 16 (11th August 2020) - Huang, Xingying; Stevenson, Samantha; Hall, Alex D.
Abstract: This study focuses on quantifying future anthropogenic changes in surface runoff associated with extreme precipitation in California's Sierra Nevada. The method involves driving a land surface model with output from a high resolution regional atmospheric simulation of the most extreme atmospheric rivers (ARs). AR events were selected from an ensemble of global climate model simulations of historical and late 21st century climate under the "high‐emission" RCP8.5 scenario. Average precipitation during the future ARs increases by ~25% but a much lower proportion falls as snow. The resulting future runoff increase is dramatic—nearly 50%, reflecting both the precipitation increase and simultaneous conversion of snow to rain. The "double whammy" impact on runoff is largest in the 2, 000–2, 500 m elevation band, where the snowfall loss and precipitation increase are both especially large. This huge increase in runoff during the most extreme AR events could present major flood control challenges for the region. Key Points: Atmospheric river storm events will become more extreme and result in intensified surface runoff along with reduced snowfall The "double whammy" impact on runoff is dramatic in the future—nearly 50% on average, easily double and higher in certain locations The disproportionately enlarged runoff during extremes could raise significant challenges for water resource management and flood control